PENGARUH HUBUNGAN ANTAR INDIVIDU DAN PEMANTAUAN DIRI TERHADAP KINERJA KARYAWAN KANWIL PT. BANK RAKYAT INDONESIA (PERSERO) BANDA ACEH - Nadiya -; Nelwita Ferliana (Jurnal Ilmiah Manajemen Muhammadiyah Aceh, 2012)
This research aims to determine the effect of interpersonal relation and self monitoring toward employee performance of Kanwil PT Bank Rakyat Indonesia (Persero) in Banda Aceh. This research conducting in the certain conditions the relationship between individual  is difficult to connecting among employees (peer). Likewise self monitoring were often miss communication to each other between employees.Sample of 80 employees of the bank were taken by the convenience sampling method. Data collection using questioner, and then the data were analyzed using multiple linear regression. The results found that the simultaneously and partially positive impact on the employee performance of Kanwil PT Bank Rakyat Indonesia (Persero) in Banda Aceh. Relation between the performance of Bank employees with the ability of the interpersonal relation and self monitoring closely pertained, which is shown by koefisien corralation ® is 0.732 or 73.20 percen.. Statistical using the F test and T test showed that both simultaneously, and the partial correlation between individual ability and self monitoring is a significant (real) on employee performance of Kanwil PT Bank Rakyat Indonesia. So that Ha  hypothesis is accepted and the other way Ho hypothesis is rejected. Therefore the leadership of the institutions must improve the capacity of employees to build relationship in the lead employees work environment and educate employees to be able and willing to make their own monitoring, this providing a direct and undirect effect with working performance will going better in accordance with the company vision and mission. Keywords: the effect of interpersonal relation,  self monitoring toward employee performance, PT Bank Rakyat Indonesia